Nauchno-metodicheskie obespechenie podgotovki sbornykh komand strany po sportivnoi gimnastiki - Cheburaev, V. S. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this paper was to analyse the system of scientific-methodical assurance of training in the national teams of Russia on sports gymnastics.